A nightmare on Elm Street ; & A nightmare on Elm Street 2 : Freddy's revenge [videorecording (DVD)]. - Craven, Wes; Saxon, John, 1935-2020; Blakley, Ronee; Langenkamp, Heather, 1964-; Depp, Johnny; Englund, Robert, 1947-; Chaskin, David; Patton, Mark, 1964-; Myers, Kim, 1966-; Rusler, Robert (New Line Cinema, 2017)
A nightmare on Elm Street: Nancy is having grisly nightmares. Meanwhile, her high-school friends, who are having the very same dreams, are being slaughtered in their sleep by the hideous fiend of their shared nightmares. When the police ignore her explanation, she herself must confront the killer in his shadowy realm.